A generation of synthesized trajectories of free moving objects for testing a set of continuous spatio‐temporal queries. (22nd June 2022) - Lee, Sanghyun; Hong, Bonghee; Kim, Woochan
Summary: Testing vessel surveillance monitoring queries requires synthesized trajectory generation data of free‐moving objects. This article presents a method for generating trajectories of free moving objects with approach, u‐turn, detour, and hover patterns to verify a set of continuous queries expressed in spatiotemporal conditions. We present an algorithm that generates simplified paths, moving patterns, and inertia‐based trajectories to make various types of trajectory patterns for a given spatiotemporal query. The experimental results show that the generated synthesized trajectory dataset can validate given spatiotemporal queries with different velocities, trajectory patterns, and travel paths.